Analisa Yuridis Penerapan Hukum Pidana Internasional Terhadap Tindak Pidana Pencucian Uang Nasional - Khamdan Khanafi (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
Its implementation and application require the use of the TPPU Law by relying on the initial crime or primary crime, the main crime according to investigators and prosecutors is part of the formal and material requirements in an event file, for its fulfillment if it is incomplete it can be considered unable to carry out prosecution by prioritizing formal processes. Money laundering cases are rarely charged under the TPPU Law because the charges given are not cumulative charges, and are only limited to the initial crime, complicated bureaucracy and difficult communication between agencies due to the integrity that does not exist between judicial institutions as a criminal justice system, lack of socialization process and regarding the anti-money laundering regime to investigators, public prosecutors, and PPATK. The problem in this study is how to apply international criminal law to money laundering. The application of International Money Laundering into Indonesia's national criminal law depends on compliance with international treaties governing transnational criminal activities. This agreement has been approved and implemented by the legal and regulatory framework of the country. This impact is seen in lawmaking, the passing of Presidential Decrees, and the legal doctrine articulated in this agreement. The Money Laundering Act serves as an example of domestic criminal legislation promulgated as a means of enforcing international conventions